An immunochromatographic assay for rapid etection of salvinorin A. Issue 4 (4th July 2017) - Paudel, Madan Kumar; Shirota, Osamu; Sakamoto, Seiichi; Morimoto, Satoshi; Tanaka, Hiroyuki
ABSTRACT: We developed an immunochromatographic assay (ICA) that enables rapid analysis of salvinorin A (Sal A) in Salvia divinorum within 10 min. The result shows that no Sal A in other samples of Lamiaceae plants was detected, but it could recognize Sal A among other substances in complex samples. The main advantage of the ICA is its high performance in combination with low cost, simplicity, and speed. Our newly developed combined ICA/indirect competitive ELISA(icELISA) system enables analysis of large numbers of samples over short periods of time without cumbersome pretreatments in complex mixtures. This method can complement other instrumental analyses for salvinorins, and could be used to deter S. divinorum abuse.